Risk factors and intraoral breast milk application for methicillin‐resistant Staphylococcus aureus colonization in surgical neonates. Issue 8 (5th August 2020) - Inoue, Mikihiro; Uchida, Keiichi; Nagano, Yuka; Matsushita, Kohei; Koike, Yuhki; Otake, Kohei; Okita, Yoshiki; Toiyama, Yuji; Araki, Toshimitsu; Kusunoki, Masato
Abstract: Background: Our previous study identified methicillin‐resistant Staphylococcus aureus (MRSA) colonization as an independent risk factor for neonatal surgical site infection. Here we introduce intraoral breast milk application (IBMA) during a fasting state to prevent MRSA colonization. We aimed to evaluate both the risk factors for MRSA colonization and the efficacy of IBMA in neonatal surgical patients. Methods: A retrospective review was performed using admission data from 2007 to 2016. Neonatal patients who underwent surgery and were tested periodically for MRSA colonization were evaluated for an association between MRSA colonization and perinatal or perioperative factors. Results: The overall incidence of MRSA colonization for the 159 patients enrolled in this study was 16.4%. Univariate analysis showed that MRSA colonization was significantly more frequent in the following patients: those with Down syndrome, those admitted on their day of birth, those in need of fasting immediately after birth, and those not receiving IBMA. Multivariate analysis showed that comorbid Down syndrome was an independent risk factor (hazard ratio: 4.6; 95% confidence interval: 1.2–19.5, P = 0.03) and implementation of IBMA was an independent preventive factor for MRSA colonization (hazard ratio: 0.4; 95% confidence interval: 0.1–0.9, P = 0.04). MRSA‐positive patients admitted significantly earlier and stayed longer preoperatively than MRSA‐negative patients. Conclusions: In neonates undergoing surgery, and patients with Down syndrome, early diagnosis after birth and a long waiting period before operation may be associated with MRSA colonization. Intraoral breast milk application may be beneficial for preventing MRSA colonization.